2010
DOI: 10.3109/17453674.2010.533936
|View full text |Cite
|
Sign up to set email alerts
|

Use of a trabecular metal implant in ankle arthrodesis after failed total ankle replacement

Abstract: Background and purposeArthrodesis after failed total ankle replacement is complicated and delayed union, nonunion, and shortening of the leg often occur—especially with large bone defects. We investigated the use of a trabecular metal implant and a retrograde intramedullary nail to obtain fusion.Patients and methods13 patients with a migrated or loose total ankle implant underwent arthrodesis with the use of a retrograde intramedullary nail through a trabecular metal Tibial Cone. The mean follow-up time was 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 20 publications
(34 reference statements)
0
49
0
2
Order By: Relevance
“…They were used in combination with an intramedullary nail passed through the cones. They noted initial subsidence of 4-5 mm but all except one of the 13 patients were satisfied with the outcome of treatment [24].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They were used in combination with an intramedullary nail passed through the cones. They noted initial subsidence of 4-5 mm but all except one of the 13 patients were satisfied with the outcome of treatment [24].…”
Section: Discussionmentioning
confidence: 92%
“…The time spent in a cast was average 15 weeks (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the series by Hopgood et al using either screws or intramedullary nail for fixation [1]. Culpan et al reported a total of 2 months in nonweight bearing cast and another month in weight bearing cast.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It will be necessary to monitor her long-term for potential talar component subsidence because of the previous massive aseptic osteolysis and because polymethyl methacrylate cement was used to affix the anterior talar component. Conversion to a tibiotalocalcaneal arthrodesis would be challenging and require use of a bulk femoral head or tibial allograft 36,39 or metallic interpositional spacer 40,41 with the known risks associated with these forms of limb salvage. The use of a fixed ankle-foot orthosis remains plausible if she develops symptoms that warrant this form of functional bracing.…”
Section: Complications and Concernsmentioning
confidence: 99%
“…In addition, poor quality or quantity of bone can preclude the placement of arthroplasty components, as there are limits in the sizes of polyethylene spacers and metal augmentation. More recently, cage and trabecular metal implant reconstructions have been introduced to act as a void filler 20,21 (Fig. 20).…”
Section: Introductionmentioning
confidence: 99%